The Effect of Organizational Commitment and Motivation on Employee Job Satisfaction in The Infrastructure Division of PT X in The Jakarta Region - Dinda Putri Amalia (Al-Makki Publisher, 2026)
This study aimed to examine the effects of organizational commitment and motivation on employee job satisfaction in the Infrastructure Division of PT X in the Jakarta Region. Job satisfaction is an important factor in improving productivity and achieving organizational success, while low job satisfaction can lead to decreased work morale, increased absenteeism, and reduced employee loyalty. This study employed a quantitative approach with descriptive and explanatory research designs. The population consisted of 80 employees in the Infrastructure Division of PT X in the Jakarta Region, and all employees were included as the research sample using a saturated sampling technique. Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination using SPSS software. The results showed that organizational commitment had a positive and significant effect on employee job satisfaction. Motivation also had a positive and significant effect on employee job satisfaction. Furthermore, organizational commitment and motivation simultaneously had a significant effect on employee job satisfaction. The coefficient of determination indicated that organizational commitment and motivation explained 53.3% of the variance in employee job satisfaction, while the remaining percentage was influenced by other variables outside the scope of this study. Therefore, companies are advised to strengthen organizational commitment through employee engagement, effective communication, and organizational culture development, while enhancing work motivation through recognition programs, career development opportunities, and a supportive work environment to continuously improve employee job satisfaction.